The man plan - Warren, Tracy Anne (Signet, an imprint of New American Library, a division of Penguin Group (USA) LLC, 2014)
When she moves into his Manhattan apartment building, Ivy Grayson determines to make billionaire financier James Jordon, whom she has loved since she was fifteen, see her as a desirable woman instead of a little girl.